2018
DOI: 10.2147/cia.s162356
|View full text |Cite
|
Sign up to set email alerts
|

Management of AO type 12C humerus proximal metadiaphyseal fractures with minimally invasive plate osteosynthesis in geriatric patients

Abstract: BackgroundTo evaluate the treatment efficacy and complications of the lateral minimally invasive plate osteosynthesis (MIPO) method in geriatric patients with a humerus diaphyseal fracture with proximal extension.Patients and methodsThe study included a total of 21 patients (18 females, 3 males; mean age 74±6.3 years, range 65–89 years) who underwent surgery with the lateral MIPO technique for a humerus diaphyseal fracture with proximal extension during the period January 2011 to December 2016. None of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Some authors have advocated fixation with complete open or minimally invasive locked plating. [26][27][28] ORIF of proximal humerus fractures in this patient population is associated with higher levels of technical difficulty, 26 outcomes that are operator dependent, 26 the possibility of subacromial impingement syndrome due to hardware prominence, 7 risk of axillary and radial nerve palsies, 28 and a two-to threefold increased risk of all complications when compared to younger patients. 40 Robinson et al presented the large series of patients treated with ORIF and found overall nonunion rate of 7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have advocated fixation with complete open or minimally invasive locked plating. [26][27][28] ORIF of proximal humerus fractures in this patient population is associated with higher levels of technical difficulty, 26 outcomes that are operator dependent, 26 the possibility of subacromial impingement syndrome due to hardware prominence, 7 risk of axillary and radial nerve palsies, 28 and a two-to threefold increased risk of all complications when compared to younger patients. 40 Robinson et al presented the large series of patients treated with ORIF and found overall nonunion rate of 7%.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 6 , 25 Moreover, ORIF does not address the common concomitant issues of glenohumeral arthritis and rotator cuff pathology, which can be found with geriatric proximal humerus fractures. 26 28 Utilizing magnetic resonance imaging analysis of proximal humerus fractures, rates of rotator cuff tears from 42% to 70% has been demonstrated, which can be associated with limited functional outcomes. 29 , 30 As a result, the current operative approach to complex proximal humerus fractures in this population has shifted largely towards RTSA utilization, with increasing literature support.…”
Section: Discussionmentioning
confidence: 99%
“…Both nailing and plating techniques have been described so far for the treatment of displaced proximal metadiaphyseal humerus fractures with reasonable results [1][2][3]6,17]. Although minimally invasive approaches can be applied using indirect methods for fracture reduction, a single extensile approach is usually necessary [1].…”
Section: Discussionmentioning
confidence: 99%
“…They mainly occur in osteoporotic bone exhibiting a bending wedge or a long spiral type with or without a large butterfly fragment [1]. A range of treatment options have been described for these fractures, ranging from nonoperative management to internal fixation techniques, including intramedullary nailing and plate fixation [1][2][3][4][5][6][7]. However, these fractures are too high for humeral bracing and adequate stability is difficult to be maintained.…”
Section: Introductionmentioning
confidence: 99%
“…However, fixation of proximal and distal fractures is not possible with the anterior opening MIPO technique. For this purpose, it has been reported in a limited number of studies that extended segment fractures could be treated by using the anatomical PHILOS plate (2,8,9). Hence, it is possible to protect the deltoid insertion, to use the distal anterior surface for fixation of the distal screws, and to move away from the radial nerve zone by applying PHILOS plates that are helically shaped manually.…”
Section: Introductionmentioning
confidence: 99%